2013
DOI: 10.1136/oemed-2012-101211
|View full text |Cite
|
Sign up to set email alerts
|

Traffic-related air pollution and prostate cancer risk: a case–control study in Montreal, Canada

Abstract: Exposure to ambient concentrations of NO2 at the current address was associated with an increased risk of prostate cancer. This novel finding requires replication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
70
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(73 citation statements)
references
References 14 publications
1
70
0
2
Order By: Relevance
“…For example, exposure to nitrogen dioxide (NO2) has been positively associated with increased airway responsiveness in asthmatic individuals after short-term exposures and respiratory illnesses in children with longer-term exposures (United States Environmental Protection Agency 2008). Other studies also found a positive correlation between NO2 and incidences of breast cancer, heart attacks and asthma (Crouse et al 2010;Parent et al 2013;Wu et al 2011). …”
Section: Background and Motivationmentioning
confidence: 98%
See 2 more Smart Citations
“…For example, exposure to nitrogen dioxide (NO2) has been positively associated with increased airway responsiveness in asthmatic individuals after short-term exposures and respiratory illnesses in children with longer-term exposures (United States Environmental Protection Agency 2008). Other studies also found a positive correlation between NO2 and incidences of breast cancer, heart attacks and asthma (Crouse et al 2010;Parent et al 2013;Wu et al 2011). …”
Section: Background and Motivationmentioning
confidence: 98%
“…Due to the scale of this study, only NO2 and particulate matter will be emphasized. (Crouse et al 2010;Parent et al 2013;Wu et al 2011). Cohort studies have also found that NO2 was associated with life-time history of asthma and wheezing, with a positive correlation between residential location and its 8 distance to a highway (Brauer et al 2007).…”
Section: Traffic-related Air Pollution and Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…As anticipated, there were significant differences between the eight experimental conditions of the 2 × 2 × 2 design, which provided information about the air quality along the two routes (conditions [5][6][7][8][9][10][11][12], and the four control groups (conditions 1-4) with regard to the degree to which participants acknowledged that they were informed about the air quality along the two routes (M = 6.01, SD = 1.54 vs. M = 3.37, SD = 1.97, on a scale from 1 [lowest level of agreement] to 7 [highest level of agreement]; F(11,585) = 37.98, p < 0.001, with all the post hoc test results in agreement with the study's assumptions).…”
Section: Mediating Effects Of Psychological Distancementioning
confidence: 99%
“…This is a concern to individuals because bad air quality decreases quality of life and increases mortality. In particular, road transportation-related air pollutants (i.e., carbon monoxide, black carbon, nitrogen dioxide, volatile organic compounds, ultrafine particles, and fine particulate matter) [5] are harmful to human health because they promote pulmonary diseases [6,7], cardiovascular diseases [8], as well as lung and prostate cancer [9,10].…”
Section: Introductionmentioning
confidence: 99%